Effects of Gymnema sylvestre extract on the pharmacokinetics and pharmacodynamics of glimepiride in streptozotocin induced diabetic rats. (5th February 2016) - Kamble, Bhagyashree; Gupta, Ankur; Moothedath, Ismail; Khatal, Laxman; Janrao, Shirish; Jadhav, Amol; Duraiswamy, B.
Abstarct: Gymnema sylvestre, important Indian traditional herbal medicine has been used for diabetes from several years and marketed as single or multi-herb formulations globally. People are consuming G. sylvestre along with conventional hypoglycemic drugs. Therefore, there is need of evidence based assessment of risk versus benefits when G. sylvestre co-administered with conventional oral hypoglycemic drugs. In present investigation, pharmacodynamics and pharmacokinetic interactions with oral hypoglycemic drug, glimepiride (GLM) was studied in streptozotocin (STZ) induced diabetic rats. A specific and rapid HPLC-ESI-MS/MS method was established for simultaneous quantification of GLM and gymnemagenin (GMG) in rat plasma. Pharmacokinetic and pharmacodynamic interaction studies were carried out in STZ induced diabetic rats after concomitant administration of 400 mg/kg of G. sylvestre extract and 0.8 mg/kg of GLM for 28 days. The developed HPLC-ESI-MS/MS method was rapid, specific, and precise. Con-comitant oral administration of G. sylvestre extract (400 mg/kg) and GLM (0.8 mg/kg) in diabetic rats for 28 days showed beneficial pharmacodynamic interactions whereas no major alterations in the pharmacokinetics parameters of GLM and GMG were observed. This interaction demonstrated in animal model implies that significant clinical outcome might occur during concomitant administration of G. sylvestre extract and GLM especially in diabetic patients and warrants further studies in the same set up. Graphical abstract: Highlights: HPLC-ESI-MS/MS method, for simultaneous determination of GMG and GLM in rat plasma. No significant pharmacokinetic of Gymnema sylvestre extract, in terms of GMG, and GLM. Significant pharmacodynamic interactions of G. sylvestre and GLM. This observation warranted further controlled clinical trials or case studies.